Optimized controller for renewable energy sources integration into microgrid: Functions, constraints and suggestions - Hannan M.A.; Tan S.Y.; Al-Shetwi A.Q.; Jern K.P.; Begum R.A. (Elsevier Ltd, 2023)
Controllers; Distributed power generation; Electromagnetic wave emission; Energy transfer; Integration; Natural resources; Optimization; Quality control; Renewable energy resources; System stability; Efficient optimisation; Environmental pollutions; Experimental validations; Integration of renewable energies; Optimisations; Optimized controllers; Renewable energy source; Renewables integrations; Integral equations